The Multicultural Dilemma : Migration, Ethnic Politics, and State Intermediation. - Williams, Michelle (Taylor and Francis, 2012)
This work seeks to explore the contemporary challenge of government in multicultural societies, drawing together a wide range of contributors to examine how ethnic difference could better understood and mediated by modern nation states. Divided into three sections, the book centres round the notion that changing patterns of migration bring escalating obstacles to integration or assimilation. In the first section, contributors focus on the theory that immigrants are the actors that catalyze contemporary multicultural dilemmas within states, with a particular focus on diaspora and how a.